Effect of Allostatic Load on hepatic steatosis and fatty liver-associated liver fibrosis - Lei Zhang; Mingyu Chen (BMC Gastroenterology)
Abstract Background The Allostatic Load Index (ALI), as a comprehensive biomarker for assessing the body’s chronic stress response, has been widely used in quantitative studies of the physiological mechanisms of stress. In this study, we systematically investigated the relationship between ALI and hepatic steatosis and fibrosis through cross-sectional analysis. Methods This study was based on the National Health and Nutrition Examination Survey (NHANES) 2017 - March 2020 dataset. The ALI was categorized into three grades of ≤ 1, 2 and ≥ 3, and after two types of missing data of covariates were processed by the deletion method and multiple interpolation, multiple linear regression and subgroup models were constructed to assess the association between ALI and hepatic steatosis / fibrosis. The mediator model was used to validate the mediating effects of hepatic steatosis, Neutrophil-to-Lymphocyte Ratio(NLR) and alcohol consumption in the ALI-hepatic fibrosis pathway. Results The study ultimately included 5,992 eligible participants, including 2,674 patients with fatty liver and 663 patients with liver fibrosis.In the fatty liver subgroup, the percentages of ALI ≤ 1, ALI = 2, and ALI ≥ 3 were 23.98%, 33.35%, and 42.67%; in the hepatic fibrosis subgroup, the above percentages were 20.11%, 26.77%, and 53.12%.Elevated ALI (≥ 3) was independently associated with higher age, lower education level, comorbidities, NLR, DII and liver-related parameters (CAP, LSM, AST) (p < 0.05).In the general sampled NHANES population, individuals with ALI ≥ 3 had 1.410× higher adjusted hepatic steatosis prevalence (Odds Ratio, 1.410(1.251–1.584)) and 1.114× higher adjusted liver fibrosis prevalence (Odds Ratio, 1.114(1.066–1.164)) compared with those with ALI ≤ 1. In a sensitivity analysis based on multiple interpolated data, a multifactorial corrected model showed that an ALI ≥ 3 was associated with a 40% increased risk of hepatic steatosis and a 10% increased risk of hepatic fibrosis (p < 0.05). Subgroup analyses showed the association between ALI = 2 and risk of fatty liver was not statistically significant in those ≥ 65 years of age (p = 0.066), whereas ALI ≥ 2 still maintained a significant association in the other subgroup (p < 0.05); ALI ≥ 3 showed a significant association with the risk of liver fibrosis in comorbidities, gender subgroups, light alcohol consumption, Non-Hispanic white, Other Race (p < 0.05). The total effect of ALI on liver fibrosis was 0.063 (p < 0.001), of which 22.6% was mediated by CAP (indirect effect: 0.014, p < 0.001) and direct effect 0.049 (p = 0.014); NLR and alcohol consumption did not show significant mediating effects (p > 0.05). Conclusion ALI is associated with liver outcomes, and systemic stress responses exacerbate the progression of liver disease. Assessing ALI is beneficial for managing fatty liver disease and hepatic fibrosis; however, further longitudinal studies are required to establish causality.